The Effectiveness and Implementation of Formative Assessment in Primary Education: A Systematic Literature Review - Ima Nurwahidah; M. Solehuddin; Ima Nurwahidah (Universitas Negeri Malang, 2026)
Although formative assessment stands as a pillar of high-quality pedagogy, its integration into Indonesian primary education remains hamstrung by persistent systemic hurdles. This systematic literature review (SLR), anchored in the PRISMA protocol, scrutinised 32 high-impact studies published from 2019 to 2024. The study’s core objectives were threefold: (1) to evaluate how specific formative strategies drive student achievement; (2) to map the variables that either facilitate or obstruct successful implementation; and (3) to propose evidence-based benchmarks tailored to the Indonesian context. Findings indicate that well-calibrated formative practices yield a substantial effect size (d = 0.38–0.78) on pupil outcomes, particularly when the feedback loop is immediate, specific, and actionable. Eight standout strategies emerged: exit tickets, Socratic questioning, peer and self-assessment, gamified digital tools, structured observations, mathematical journals, and mini-whiteboards. Despite these advantages, the transition is often stalled by a trifecta of barriers: gaps in teacher competence, heavy administrative overhead, and infrastructure deficits. Ultimately, this review offers a roadmap for embedding contextualised, research-backed assessment frameworks into Indonesian primary classrooms